ANALISIS FAKTOR AKADEMIK DAN NON-AKADEMIK YANG MEMPENGARUHI TINGKAT KELULUSAN MAHASISWA - Wilda Rahmadani (Griya Journal of Mathematics Education and Application, 2025)
This study aims to analyze the influence of academic and non-academic factors on student graduation rates. The academic factors studied included study hours, lecture attendance, and the number of Semester Credit Units (SKS), while non-academic factors included organizational involvement and a supportive learning environment. The quantitative approach used was multiple linear regression and logistic regression. The study was conducted with 35 respondents from several study programs at the Faculty of Mathematics and Natural Sciences, State University of Medan. The results showed that study hours, lecture attendance, and a supportive learning environment had a positive and significant influence on student academic achievement. Conversely, organizational involvement and the number of credits taken did not show a significant influence. The coefficient of determination (R²) of 0.761 indicates that 76.1% of the variation in student academic achievement can be explained by these five variables, while the remaining 23.9% is influenced by factors outside the model. Thus, it can be concluded that student academic success is significantly influenced by study discipline, lecture attendance, and social support from the surrounding environment.